Comparative Analysis of the Burden of Bipolar Disorder Among Individuals Aged 15–49 Years in China and Globally, 1990–2021: An Ecological Trend Analysis Based on GBD 2021 - Guocong Liang; Li Li; Zheng Gong; Weier Chen; Peifeng Cai; Helei Cheng; Lili Cui; Yujie Cai (Health Science Reports, 2026)
ABSTRACT Background and Aims Bipolar disorder (BD) imposes a substantial and long‐lasting public health burden, particularly during adolescence and early adulthood. Previous Global Burden of Disease (GBD) studies have described global patterns, but the burden in China among individuals aged 15–49 years has not been sufficiently contextualized using decomposition and socio‐demographic index (SDI)‐stratified comparisons. This study aimed to describe modeled trends in incidence, prevalence, and disability‐adjusted life years (DALYs) for BD in China and globally from 1990 to 2021. Methods This ecological trend analysis used publicly available, anonymized GBD 2021 estimates for BD among individuals aged 15–49 years. Counts and rates of incidence, prevalence, and DALYs were extracted for China, the global population, and SDI regions, stratified by age and sex. Average annual percent change (AAPC) summarized temporal patterns. Decomposition analysis was used to separate changes in case counts into contributions from population size, age structure, and epidemiological change. Estimates are reported with 95% uncertainty intervals (UIs), and no null‐hypothesis significance testing was used. Results In 2021, global incident BD cases reached 1.63 million, whereas the global incidence rate changed little from 1990. In China, modeled incident cases decreased from 108,291 to 96,004, and the incidence rate decreased from 16.24 to 14.47 per 100,000. Global prevalence rose from 16.74 million to 25.28 million cases, whereas China showed a smaller increase from 1.58 to 1.60 million. Global DALYs increased from 3.65 to 5.50 million, while China increased slightly from 349,047 to 354,724. Decomposition suggested that global increases were mainly associated with population size, whereas changes in China were more strongly related to age structure. In 2021, China had lower modeled rates than the global estimate and all SDI groups examined. Females consistently had slightly higher rates than males. Conclusion Modeled GBD estimates suggest that the burden of BD among individuals aged 15–49 years in China remained below global and SDI‐stratified estimates, with slower increases in prevalence and DALYs. These lower estimates should be interpreted cautiously because they may reflect underdiagnosis, sparse input data, and modeling assumptions rather than a truly lower burden. The findings support cautious, context‐specific strategies emphasizing early detection, diagnostic accuracy, and sex‐sensitive mental health services.